2002
DOI: 10.1093/carcin/23.7.1229
|View full text |Cite
|
Sign up to set email alerts
|

The human OGG1 DNA repair enzyme and its association with orolaryngeal cancer risk

Abstract: The human OGG1 (hOGG1) gene encodes a DNA glycosylase that is involved in the excision repair of 8-hydroxy-2'-deoxyguanine (8-OH-dG) from oxidatively-damaged DNA. To determine whether hOGG1 plays a role in risk for orolaryngeal cancer, we screened normal orolaryngeal tissue specimens for hOGG1 expression and assessed the role of the hOGG1 Ser326Cys polymorphism in risk for orolaryngeal cancer. hOGG1 expression was determined by reverse transcription-polymerase chain reaction of total RNA from aerodigestive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 37 publications
7
114
2
1
Order By: Relevance
“…The methodology was also validated using 96 oral buccal cell genomic DNA samples from cancer-free community residents. Details of this study have also been reported previously [17]. DNA from both of these studies was extracted using a commercial kit (Qiagen Inc., Valencia, CA).…”
Section: Ugt2b17 Deletion Polymorphism Genotyping Methodologymentioning
confidence: 99%
“…The methodology was also validated using 96 oral buccal cell genomic DNA samples from cancer-free community residents. Details of this study have also been reported previously [17]. DNA from both of these studies was extracted using a commercial kit (Qiagen Inc., Valencia, CA).…”
Section: Ugt2b17 Deletion Polymorphism Genotyping Methodologymentioning
confidence: 99%
“…DOI 10.1002/em well as metabolic homeostasis. In this regard, the Ser326Cys mutation has been associated with human lung squamous cell carcinomas [Lu et al, 1997;Chevillard et al, 1998;Sugimura et al, 1999;Wikman et al, 2000;Le Marchand et al, 2002;Paz-Elizur et al, 2003;Okasaka et al, 2009], orolaryngeal [Elahi et al, 2002], esophageal [Xing et al, 2001], kidney [Chevillard et al, 1998;Audebert et al, 2000Audebert et al, , 2002, and gastric cancers [Farinati et al, 2008]. Recently, two studies have also reported an association between the Ser326Cys mutation and increased body mass index and susceptibility to Type II diabetes [Daimon et al, 2009;Thameem et al, 2010].…”
Section: Nth1mentioning
confidence: 99%
“…Studies indicated a role of the HOGG1 Ser326Cys polymorphism in many cancers including oro-laryngeal cancer (Elahi et al, 2002;Yang et al, 2008), esophageal cancer (Xing et al, 2001), lung cancer (Lan et al, 2004), gastric cancer (Hanaoka et al, 2001), renal cell carcinoma (RCC) (Zhao et al, 2011), gallbladder cancer (Jiao et al, 2007), bladder cancer (Arizono et al, 2008), prostate cancer (Zhang et al, 2010) and acute lymphoblastic leukemia (Stanczyk et al, 2011).…”
mentioning
confidence: 99%